Clown Performance in the European One-Ring Circus - Little, Kenneth (Culture, 1981)
An attempt is made to interpret a clown act, a musical entree, as it was performed in various European one-ring circuses during the earlier part of this century. This interpretation relies on the fact that clowns, as circus actors, attempt to re-create the ordinary, everyday world in a ludic form by scrutinizing our expressions of what is ordinary and everyday. In effect, clowns “defamiliarize” many of our habits of perception. In this way clowns are saying something about our everyday world in a way in which their audience can reflect and thereby come to a better understanding of the world in which they live.